RETRACTED: Fundamentals of forecasting explosive gas accumulation formation in working areas of coal mines - Pekarchuk Danil; Skripnik Igor; Panov Sergey; Kaverzneva Tatyana; Gorbunova Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001